GROWTH AND WOOD TRAITS EVALUATION OF 15-YEAR-OLD TENGKAWANG (Shorea spp.) TREE STANDS IN GUNUNG WALAT UNIVERSITY FOREST, WEST JAVA, INDONESIA - Fifi Gus Dwiyanti; Rosdayanti, Henti; Yulita, Kusumadewi Sri; Rachmat, Henti Hendalastuti; Ayyasy, Yahya; Muharam, Karima Fauziah; Rahman, Mohamad Miftah; Adzkia, Ulfa; Siregar, Iskandar Zulkarnaen (Indonesian Journal of Forestry Research, 2024)
Gunung Walat University Forest (GWUF) in Sukabumi Regency, Indonesia, plays a crucial role in providing various ecosystem services. Five important Shorea trees, i.e., S. stenoptera, S. mecisopteryx, S. pinanga, S. palembanica, and Shorea leprosula have been planted in GWUF as an effort for its conservation and object of research. An evaluation of the adaptability and suitability of these species to the GWUF ecosystem, as well as their wood characteristics, needs to be carried out regularly. Therefore, the study aimed to examine the growth performances and physical wood properties of five Shorea species, i.e., Shorea stenoptera, S. mecisopteryx, S. pinanga, S. palembanica, and S. leprosula at the age of 15-year-old planted in GWUF. The results indicated that S. leprosula exhibited the best growth performance in terms of average diameter (19.64 cm), volume (0.27 m3), slenderness (126.58), and wood density (0.94 g/cm3), and S. stenoptera showed the best performance in average height (23.35 m). While the poor performance was shown by S. palembanica in terms of average diameter (6.73 cm), height (11.15 m), volume (0.02 m3), wood density (0.87 g/cm3), and specific gravity (0.45), and S. stenoptera in terms of average slenderness (202.73). In addition, significant differences in tree height, diameter, volume, wood density, specific gravity, and moisture content were found in S. palembanica compared with other species. The relationship between the growth and physical wood properties parameters varied between species. The study revealed that planting the five Shorea species in GWUF is suitable for increasing vegetation cover and conserving the species.